LITERASI MEDIA SOSIAL PADA PEMUDA DI DESA SORO KABUPATEN BIMA - Mimin Napsiatul Mutmainnah; Rahmatia Rahmatia; Hasbi Hasbi (Jurnal Dakwah Tabligh, 2020)
The research purpose is to outlines and analyzes social media literacy rates on youth in Bima District. The research was conduct in Soro village. This research classified as a quantitative study with a survey approach. Sampling determined by the probability sampling method. Data collection using questionnaires and document studies. The data analysis technique used is the scoring method with the Likert scale. The results showed that in general the level of social media literacy in youth in Lariti Beach tourism area precisely in the Soro Village classified as a medium level which is the ability of Technical skills already relatively high, the ability of critical understanding is medium, and the ability of communicative abilities classified as medium.